2020
DOI: 10.3390/ijns6030075
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing Newborn Screening Laboratory Proficiency Test Results Using the CDC NSQAP Reference Materials

Abstract: Newborn screening (NBS) laboratories cannot accurately compare mass spectrometry-derived results and cutoff values due to differences in testing methodologies. The objective of this study was to assess harmonization of laboratory proficiency test (PT) results using quality control (QC) data. Newborn Screening Quality Assurance Program (NSQAP) QC and PT data reported from 302 laboratories in 2019 were used to compare results among laboratories. QC materials were provided as dried blood spot cards which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…NBS using MS/MS is generally regarded a semi-quantitative assay as some analytes are isobaric and QC materials are not available for certain analytes, which is another reason for the discrepancy in the quantitative results and cutoffs among laboratories [ 30 ]. To reduce assay-related biases, harmonization of quantitative results, allowing head-to-head comparison among laboratories, would be ideal [ 31 ]. In the qualitative accuracy evaluation using KEQAS PT materials, there was only one sample for each analyte with disagreement.…”
Section: Discussionmentioning
confidence: 99%
“…NBS using MS/MS is generally regarded a semi-quantitative assay as some analytes are isobaric and QC materials are not available for certain analytes, which is another reason for the discrepancy in the quantitative results and cutoffs among laboratories [ 30 ]. To reduce assay-related biases, harmonization of quantitative results, allowing head-to-head comparison among laboratories, would be ideal [ 31 ]. In the qualitative accuracy evaluation using KEQAS PT materials, there was only one sample for each analyte with disagreement.…”
Section: Discussionmentioning
confidence: 99%
“…Data harmonization is also suggested to reduce false-negative and false-positive results, correct for method differences, and achieve greater uniformity of results and clinical conclusions [ 3 , 4 , 6 , 24 , 25 ]. Harmonization, considered to be a “holy grail” [ 25 ], facilitates scaled comparisons and is “the process of recognizing, understanding, and explaining differences while taking steps to achieve uniformity of results, or at minimum, a means of conversion of results such that different groups can use the data obtained from assays interchangeably” [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some NBS labs have successfully used multiples of the median (MoM) to harmonize results for MPS I [ 27 , 28 ], TREC [ 29 ], and in a large study involving homocystinuria results from 32 NBS programs covering 18 countries [ 17 ]. Other methods have also been employed, such as using quality control materials and regression equations to harmonize NBS proficiency testing (PT) results for amino acids and acylcarnitines [ 24 ]. Barriers to harmonization efforts have been attributed to differences in instrumentation, methods used, analyte recovery, reagents, cutoffs, and populations screened, which can make result comparisons problematic [ 10 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that interlaboratory variation can be substantially reduced by the use of common stable isotope IS (4), and another study has shown that retrospectively harmonizing screening results to the CDC's Newborn Screening Quality Assurance Program internal quality control (IQC) material reduced interlaboratory variation in a set of proficiency testing samples (5).…”
Section: Introductionmentioning
confidence: 99%